Jobs and Land Use within Cities : A Survey of Theory, Evidence, and Policy - Goswami, Arti Grover (World Bank, Washington, DC, 2015)
Over the last century, the urban spatial structure of cities has transformed dramatically from the traditional monocentric configuration to varying forms of decentralized organization. This paper reviews the theory and empirical evidence to understand the urban morphology of jobs and land use within a city. This survey highlights four broad insights: (i) The evolution of monocentric to polycentric centers has been accompanied by structural changes in the city. (ii) The internal geography of a city is an outcome of the trade-off between the pull from agglomeration economies and the push from congestion. (iii) The presence of externalities implies that the equilibrium spatial organization achieved by profit-maximizing firms may not necessarily be optimal. This justifies the role of public policy in addressing the associated market failures. (iv) The productive edge and competitiveness of a city can be enhanced by introducing policies that increase the overall connectivity to take advantage of economic opportunities across the metropolitan area. The survey also puts together a wide range of policy instruments that are useful in closing the gap between equilibrium urban spatial structure and the optimal outcome.